Joint transmit and receive antenna selection in mimo systems for maximize channel capacity - LAN Peng1; LIU Ju1; XU Hong-ji1; SUN Feng-gang1 (Tongxin xuebao)
Based on the analysis of the channel capacity,the equation about the increase of the channel capacity was derived when one more pair of transmit and receive antennas were added.By analyzing this equation,a joint transmit and receive antennas selection algorithm with low complexity were proposed when there were the same number of RF chains at both of the transmitter and receiver side.The simulation results illustrate that the new algorithm outperforms the other existing algorithms with lower complexity and it approaches the optimal algorithm most.